2017
DOI: 10.7150/jca.19062
|View full text |Cite
|
Sign up to set email alerts
|

Low Preoperative albumin-to-globulin ratio Predict Poor Survival and Negatively Correlated with Fibrinogen in Resectable Esophageal Squamous Cell Carcinoma

Abstract: Background: Although various inflammation-based indexes in esophageal carcinoma have been documented, but the prognostic value of the albumin-to-globulin ratio(AGR) and its correlation with fibrinogen in resectable ESCC remain unknown.Methods: The levels of pre-treatment serum common acute phase proteins (including CRP, albumin and fribrinogen) were retrospectively analyzed in 447 patients with ESCC who underwent surgical resection at our department. The prognostic value was explored by univariate and multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Via the interaction of a ligand-receptor mechanism involving a wide range of immune cells such as monocytes and microphages, fibrinogen also plays a key role in regulating reactions within the inflammation cascade 30 , 33 . Furthermore, the prominent role of fibrinogen in predicting prognosis has been reported in a large number of cancers, including HCC, advanced esophageal squamous cell carcinoma, renal cell carcinoma, and esophageal squamous cell carcinoma 23 , 24 , 34 - 37 . CRP, which is another prominent system inflammation response factor, has been reported to be closely associated with prognosis in HCC, pancreatic cancer, renal cancer, gastric cancer, lung cancer and lymphoma 26 - 27 , 38 - 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Via the interaction of a ligand-receptor mechanism involving a wide range of immune cells such as monocytes and microphages, fibrinogen also plays a key role in regulating reactions within the inflammation cascade 30 , 33 . Furthermore, the prominent role of fibrinogen in predicting prognosis has been reported in a large number of cancers, including HCC, advanced esophageal squamous cell carcinoma, renal cell carcinoma, and esophageal squamous cell carcinoma 23 , 24 , 34 - 37 . CRP, which is another prominent system inflammation response factor, has been reported to be closely associated with prognosis in HCC, pancreatic cancer, renal cancer, gastric cancer, lung cancer and lymphoma 26 - 27 , 38 - 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple researches have focused on the prominent roles of fibrinogen and CRP in the prognostic prediction 23 - 28 .However, in the researches by Zhang X et al and Xiao-Hui Li et al, the value of serum fibrinogen was only researched in the training cohort thus absenting the validation study 23 , 24 . The main advantages of the current study were that a relatively large HCC population who underwent curative resection was involved, and the findings in the training cohort were further verified in the validation cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Cho et al [15] in the study that was assessed Recently, the association of fibrinogen and albumin started to be investigated in coronary artery disease and in many cancer cases. In many cancer diseases such as hepatocellüler ca [17], breast ca [19], non-squamöz eausofagial ca [20] and lung ca [21], fibrinogen to albumin ratio was calculated and high FAR was associated with bad prognosis. In one of the rare studies on the rate of fibrinogen albumin in coronary artery disease, Karahan et al [22] showed that FAR is significantly related to SYNTAX Score in predicting the severity of CAD in patients with ST-elevation myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, some investigators have reported that pretreatment AFR could serve as a promising biomarker to predict survival in several cancers such as the non-small cell lung cancer (NSCLC), breast cancer, squamous cell carcinoma of esophagus (SCCE) and hepatocellular carcinoma and low AFR predicts poorer survival for cancer patients. [7][8][9][10] Albumin and fibrinogen are both inflammatory and immunological proteins which involve in the initiation, growth and metastasis of tumors. 7 Hence, we hypothesized that circulating AFR could serve as an effective indicator to predict the prognosis and contribute to the formulation of therapeutic strategy for ESCC patients.…”
Section: Introductionmentioning
confidence: 99%